Analysis of pharmaceutical adulterants in plant food supplements by UHPLC-MS/MS - Paíga, Paula (2019)
A method based on the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) extraction and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) was successfully developed and validated for the analysis of 26 pharmaceutical compounds belonging to different therapeutic classes (anorexics, stimulants, anxiolytics, antidepressants and laxatives), which are all prone to be illegally added into weight-loss plant food supplements (PFS) for their pharmacological activity. Internal standard calibration with six isotopically labelled compounds rendered good linearity in the range of 5 to 1000μg/l, depending on the compound, and good sensitivity with limits of quantification in the range of 0.02-9.80μg/l. Recoveries were assessed for all the 16 samples analysed and were found between 70% and 120% for over 90% of the analytes. The average recovery value was 90.8%, for the different studied matrices (liquids, liquid ampoules, tablets and capsules), with RSD values lower than 10% for all forms. The changes introduced to the QuEChERS procedure maintained the good performance characteristics of the extraction method while preserving the chromatographic system for the introduction of unwanted matrix compounds. Synephrine was the only compound detected and quantified in one sample, but at a very low concentration (768μg/l) and its presence may be due to the plant extracts used in the formulation, as synephrine is known to be a natural constituent of Citrus aurantium amara. Despite none of the 16 evaluated samples were found to be adulterated by the illegal addition of the drugs included in this work, the developed methodology can be very useful for monitoring the adulteration of weight-loss PFS.